Mental Health and Immigrant Perceptions of Inclusion - Samantha Chapa; Jeronimo Cortina (Psychology International)
Previous research on immigrant integration indicates that contextual factors, such as access to health services, often lead to varying levels of immigrant incorporation and feelings of inclusion. Research has demonstrated the link between inclusion and physical health but less is known about the connection between mental health and immigrant inclusion. In this study, we examine the impact of the prevalence of mental health issues at the county level on immigrants’ perceptions of inclusion. We propose that a lower prevalence of mental health issues at the county level is associated with improved perceptions of inclusion among immigrants. To explore this relationship, we analyze data from the Kaiser Family Foundation, which covers feelings of immigrant inclusion from a racially and geographically diverse sample of immigrants across the United States. We pair these data with CDC PLACES data on the crude prevalence of mental health issues at the county level. Our findings reveal an association between the crude prevalence of mental health issues at the county level and immigrants’ feelings of inclusion. Through this analysis, we underscore the significance of understanding the contextual determinants that shape migrants’ perceptions of inclusion.